Efficacy of curcumin gel as an adjunct to scaling and root planing on salivary procalcitonin level in the treatment of patients with chronic periodontitis: a randomized controlled clinical trial - Reham Abdel-Fatah; Bassant Mowafey; Azza Baiomy; Samah Elmeadawy (BMC, 2023)
Abstract The aim of the study To evaluate the effect of curcumin gel combined with scaling and root planing (SRP) on salivary procalcitonin in periodontitis treatment. Materials and methods seventy patients were selected from the Department of Oral Medicine and Periodontology, Faculty of Dentistry, Mansoura University, and sixteen patients were excluded. Patients in groups II and III included stage II grade A periodontitis. The participants were classified into three groups: group I as a negative control group (individuals with healthy gingiva), group II (SRP) were treated with SRP, and group III (curcumin gel) which was applied weekly for four weeks after SRP. Clinical indices (plaque index (PI), gingival index (GI), clinical attachment level (CAL), and probing depth (PD)) and saliva samples for procalcitonin (PCT) assessment using an enzyme-linked immunosorbent assay (ELISA) test were collected and measured at both baselines and after six weeks. Results This randomized controlled clinical trial registered on ClinicalTrials.gov (NCT05667376) and first posted at 28/12/2022 included Fifty-four patients (20 male; 34 female). Regarding the age and sex distribution, there was no statistically significant difference between the three studied groups (p > 0.05). There was no significant statistical difference regarding PI, GI, PPD, and CAL between group II and group III at baseline p (> 0.05). However, there was a significant statistical difference regarding the clinical parameters at baseline of both group II and group III as compared to group I (p ≤ 0.05). At six weeks after treatment, group III showed greater improvement in the PI, PD, and CAL as opposed to group II (p ≤ 0.05). Regarding PCT values, at baseline, there wasn't a statistically significant difference between group II and group III (p > 0.05). However, there was a significant statistical difference between group II, group III, and group I (p ≤ 0.05). At six weeks after treatment, there was a statistically significant decrease in PCT levels of both group II and III (p ≤ 0.05). Conclusion The application of curcumin gel was found to have a significant effect on all clinical indices as opposed to SRP.